Direct Evaluation of Myocardial Viability and Stem Cell Engraftment Demonstrates Salvage of the Injured Myocardium. Issue 7 (27th March 2015) - Kim, Paul J.; Mahmoudi, Morteza; Ge, Xiaohu; Matsuura, Yuka; Toma, Ildiko; Metzler, Scott; Kooreman, Nigel G.; Ramunas, John; Holbrook, Colin; McConnell, Michael V.; Blau, Helen; Harnish, Phillip; et al.
<x xml:space="preserve">Abstract</x> Rationale: The mechanism of functional restoration by stem cell therapy remains poorly understood. Novel manganese-enhanced MRI and bioluminescence reporter gene imaging were applied to follow myocardial viability and cell engraftment, respectively. Human-placenta–derived amniotic mesenchymal stem cells (AMCs) demonstrate unique immunoregulatory and precardiac properties. In this study, the restorative effects of 3 AMC-derived subpopulations were examined in a murine myocardial injury model: (1) unselected AMCs, (2) ckit+AMCs, and (3) AMC-derived induced pluripotent stem cells (MiPSCs). Objective: To determine the differential restorative effects of the AMC-derived subpopulations in the murine myocardial injury model using multimodality imaging. Methods and Results: SCID (severe combined immunodeficiency) mice underwent left anterior descending artery ligation and were divided into 4 treatment arms: (1) normal saline control (n=14), (2) unselected AMCs (n=10), (3) ckit+AMCs (n=13), and (4) MiPSCs (n=11). Cardiac MRI assessed myocardial viability and left ventricular function, whereas bioluminescence imaging assessed stem cell engraftment during a 4-week period. Immunohistological labeling and reverse transcriptase polymerase chain reaction of the explanted myocardium were performed. The unselected AMC and ckit+AMC–treated mice demonstrated transient left ventricular functional improvement. However, the MiPSCs exhibited a significantly greater increase in left ventricular function compared with all the other groups during the entire 4-week period. Left ventricular functional improvement correlated with increased myocardial viability and sustained stem cell engraftment. The MiPSC-treated animals lacked any evidence of de novo cardiac differentiation. Conclusion: The functional restoration seen in MiPSCs was characterized by increased myocardial viability and sustained engraftment without de novo cardiac differentiation, indicating salvage of the injured myocardium.